Enhancement of thermoelectric power of PbTe:Ag nanocomposite thin films. Issue 33 (13th March 2015) - Bala, Manju; Gupta, Srashti; Tripathi, Tripurari S.; Varma, Shikha; Tripathi, Surya K.; Asokan, K.; Avasthi, Devesh K.
Abstract : Formation of nanostructures results in the enhancement in thermoelectric power of PbTe:Ag thin films. Abstract : The present study focuses on the enhancement of thermoelectric power of PbTe:Ag nanocomposite thin films, synthesized by the thermal evaporation technique. Thermoelectric measurements were carried out from room temperature to 400 K. It is observed that Ag addition improves the thermoelectric power and crystalline nature of the PbTe thin films. Synchrotron based X-ray diffraction was performed to confirm the phases of the Pb–Ag–Te alloy. This was further reconfirmed by X-ray photoelectron spectroscopy (XPS) and showed the precipitation of Pb on the surface of the PbTe:Ag films. The enhancement of thermoelectric power is thus attributed to the formation of Ag2− x Te alloy and the precipitation of Pb nanostructures on the surface. The origin of such enhancement is understood based on the phenomenon of energy dependent filtering of charge carriers.